The Visual Invention Practices of STEM Researchers: An Exploratory Topology. (February 2015) - Walsh, Lynda; Ross, Andrew B.
This article presents results from a qualitative pilot survey of science, technology, engineering, and math (STEM) researchers concerning techniques used to create graphics for research articles. The survey aimed to induce a methodological vocabulary for a larger project designed to describe and improve STEM visual literacy for nonexperts. However, the survey also revealed interesting problems for investigation—chief among them a mismatch between STEM visual pedagogy and praxis. In addition, participants supplied a handlist of STEM visual communication texts that have informed their praxis. Survey results are presented in the form of a topology—a frequency-based representation of the topics framing participants' discussion of STEM visual invention.